The Importance of Educational Facilities and Infrastructure Planning - Eka Cahya Sari Putra; Fitri Nurmahmudah; Aliyah Rasyid Baswedan (Institut Agama Islam Negeri Palopo, 2025)
Educational facilities and infrastructure in schools are highly valued because they are key supporting factors in supporting an effective, efficient, and high-quality learning process. Without adequate facilities and infrastructure, educational goals are difficult to achieve optimally. Therefore, their provision must be a top priority in school management and education policy. The purpose of this study is to explore the planning of educational infrastructure. The method used is qualitative. Data collection techniques using interviews to school principals and teachers. The research was conducted at SD Muhammadiyah Prambanan. The analysis was conducted with the help of Atlas.ti software version 23. The results of the study showed that the planning of infrastructure facilities in elementary schools includes needs analysis, budget allocation, procurement based on priorities, maintenance, and demolition. This research recommendation is addressed to all elementary schools as part of being able to develop infrastructure facilities based on needs.